Uncovering markers for downy mildew resistance in grapevine through mass spectrometry-based metabolomics - Maia,Marisa (2018)
Downy mildew is a major threat to the wine industry and the development of hybrids between Vitis vinifera and wild resistant Vitis species is a promising strategy to cope with this disease. The discovery of metabolic markers associated with grapevine resistance is paramount. In this work we aim at speeding up the assignment of innate resistance to downy mildew in grapevine cultivars by applying high-resolution mass-spectrometry- based untargeted metabolomics as a profiling and resistance marker discovery method. We compared the susceptible cultivar Trincadeira with the more resistant one Regent. Both cultivars could be easily discriminated based on their metabolic profile and we found several peak features exclusive of each variety.